The Relationship between Adolescent Characteristics and Adolescent Health Knowledge in the RW 08 Area, Wetan Garut City Village - Shalahuddin, Iwan; Rosidin, Udin (Universitas Muhammadiyah Surakarta, 2024)
Pendahuluan: Remaja menghadapi masalah yang sangat kompleks selama masa transisi mereka. Problem seksualitas seperti perilaku seks pranikah, HIV/AIDS, infeksi menular seksual, dan NAPZA adalah masalah yang paling umum di kalangan remaja. Metode: Penelitian ini menggunakan metode survey dengan desain penelitian deskriptif kuantitatif. Jumlah populasi dalam penelitian ini adalah sebanyak 79 remaja dengan usia 15 – 18 tahun RW 08 di Kelurahan Kota Wetan. Hasil: sebanyak 24 remaja (31%) masih ada yang memliki pengetahuan kurang tentang penyakit menular seksual, 19 remaja (24,1%) memiliki pengetahuan yang kurang terkait penyakit HIV/AIDS dan 8 remaja (10,3%) memiliki pengetahuan yang kurang terkait kesehatan reproduksi, serta sebanyak 11 remaja (13,8%) memiliki pengetahuan yang kurang terkait NAPZA. Simpulan: tingkat pengetahuan remaja di RW 08 Kelurahan Kota Wetan masih ada yang berpengatahuan kurang tentang penyakit infeksi menular seksual, penyakit HIV/AIDS, kesehatan reprodukasi serta tentang NAPZA. Hal tersebut beresiko terjadinya kejadian penyakit sesuai variabel dan berpotensi bisa melakukan penyalahgunaan NAPZA. Introduction: Adolescents face very complex problems during their transition period. Sexuality problems such as premarital sex behavior, HIV/AIDS, sexually transmitted infections, and drug abuse are the most common problems among adolescents. Method: This study uses a survey method with a quantitative analytical research design. The total population in this study is 79 adolescents aged 15 – 18 years. Results: As many as 24 adolescents (31%) still have insufficient knowledge about sexually transmitted diseases, 19 adolescents (24.1%) have insufficient knowledge related to HIV/AIDS and 8 adolescents (10.3%) have insufficient knowledge related to reproductive health, and as many as 11 adolescents (13.8%) have insufficient knowledge related to drugs. Adolescent gender and employment status have a significant relationship with adolescent knowledge levels. Conclusion: That the level of knowledge of adolescents in RW 08 Wetan City Village is still in the category of lack of knowledge about adolescent health knowledge. Characteristics of adolescents by gender and occupation have a significant relationship with adolescent health knowledge, while adolescent characteristics by age have no relationship with adolescent health knowledge level.